Study of staphylococcus aureus in the nasal and oral cavities of dentistry students - Pires, Mariana Faria (2021)
Staphylococcus aureus permanently and asymptomatically colonizes 30% of the population, causing most nosocomial and community-acquired infections. The nostrils are considered its preferred host habitat and the main reservoir for transmission. However, the oral cavity has also demonstrated to be an ideal starting point for auto-infection and transmission.